1 - Africa’s Socioeconomic Development in the Age of New Technologies: Exploring Issues in the Debate - Levi Obijiofor, (Africa Media Review, 2008)
New technologies are perceived as the engines that drive socioeconomic development across the world. However, the extent of the availability, use and impact of new technologies on the socioeconomic development of Africa remains a subject of research investigations. Research on the impact of new technologies on the socioeconomic development of Africa is critical to the development of knowledge and the official policy for social change in Africa.